2023
DOI: 10.1002/cam4.5734
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peroxisome proliferator‐activated receptor‐γ activating angiotensin receptor blocker on outcomes of patients receiving immunotherapy

Abstract: Background Certain angiotensin receptor blockers (ARBs) have peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) activation property, which has been associated with improved programmed cell death ligand 1 blockade and cytotoxic T lymphocyte‐mediated antitumor activity. Methods We conducted a retrospective cohort study to investigate the impact of PPAR‐γ‐activating ARBs on patient survival in patients treated with immune checkpoint inhibitors (ICIs) across all types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Additionally, it has been found that some ARBs are peroxisome proliferator-activated receptor- γ (PPAR- γ) and increase PD-1 blockade as well as cytotoxic T lymphocyte‐mediated antitumor activity ( 50 , 51 ). A retrospective study (n=167) was conducted to assess the impact of combining PPAR- γ activating ARBs and PD-1 blockade on survival of patients with different types of cancer was conducted ( 52 ). Compared to patients who were only treated with PD-1 blockade, patients who also received PPAR- γ activating ARBs showed both improved progression free survival and overall survival and had about a 50% reduction in mortality rates and disease progression.…”
Section: Interventions That Might Enhance Ici Efficacymentioning
confidence: 99%
“…Additionally, it has been found that some ARBs are peroxisome proliferator-activated receptor- γ (PPAR- γ) and increase PD-1 blockade as well as cytotoxic T lymphocyte‐mediated antitumor activity ( 50 , 51 ). A retrospective study (n=167) was conducted to assess the impact of combining PPAR- γ activating ARBs and PD-1 blockade on survival of patients with different types of cancer was conducted ( 52 ). Compared to patients who were only treated with PD-1 blockade, patients who also received PPAR- γ activating ARBs showed both improved progression free survival and overall survival and had about a 50% reduction in mortality rates and disease progression.…”
Section: Interventions That Might Enhance Ici Efficacymentioning
confidence: 99%